See, hear and the phenomenological attitude (Research, Society and Development, 2021)
This article consists of a bibliographic research and a reflection about our understanding condition in the world, focusing on two possible ways of understanding, relating and acting in the world, based on the metaphors of seeing and hearing. Seeing is associated with activity, with control, possession, fragmentation and dominion over things. Listening, on the other hand, characterizes more the receptive, welcoming, integrating attitude, which allows to be. We show that in the western tradition there is the primacy of vision over listening, so that we gradually strive to place reality within the limits of our projects and representations, that is, we objectify the world, things and ourselves. What we know as phenomenology in the 20th century is an awareness of the possibility of going back to the living and integrated experience of things. This is not a call for the denial and suppression of our prevailing attitude, but for the development of a willingness to let things say their own words, in order to provide a dialogue between the cultural acquisitions historically available and what is offered here and now, in its occasionality and in the flow and interconnection of life in the world. A dialogue between representations and things themselves; between seeing and hearing.